Dextramabs: A Novel Format of Antibody‐Drug Conjugates Featuring a Multivalent Polysaccharide Scaffold - Hendrik Schneider; Lukas Deweid; Thomas Pirzer; Desislava Yanakieva; Simon Englert; Bastian Becker; Dr. Olga Avrutina; Prof. Dr. Harald Kolmar (ChemistryOpen, 2019)
Abstract Antibody‐drug conjugates (ADCs) are multicomponent biomolecules that have emerged as a powerful tool for targeted tumor therapy. Combining specific binding of an immunoglobulin with toxic properties of a payload, they however often suffer from poor hydrophilicity when loaded with a high amount of toxins. To address these issues simultaneously, we developed dextramabs, a novel class of hybrid antibody‐drug conjugates. In these architectures, the therapeutic antibody trastuzumab is equipped with a multivalent dextran polysaccharide that enables efficient loading with a potent toxin in a controllable fashion. Our modular chemoenzymatic approach provides an access to synthetic dextramabs bearing monomethyl auristatin as releasable cytotoxic cargo. They possess high drug‐to‐antibody ratios, remarkable hydrophilicity, and high toxicity in vitro.